Investigation of dielectric and mechanical properties of Lignocellulosic Rice Husk Fibril for high and medium voltage electrical insulation applications - T. Rajamanikandan; S. Banumathi; B. Karthikeyan; R. Palanisamy; Mohit Bajaj; Hossam M. Zawbaa; Salah Kamel (Journal of Materials Research and Technology, 2023)
The insulating material is made from rice husk and epoxy resin which are ecologically friendly and incredibly durable. When coarse Rice husk is mechanically disintegrated, fibrils are formed. By weaving together fibrillated threads, and robust biodegradables, lightweight dielectric fibers are created. Then the Composites are examined utilizing a blend of agave Rice husk fibers (10–35%) and an epoxy resin solution. The Chemical treatment of the Rice husk fibers increases the composites’ mechanical strength and electrical insulating properties. The tensile strength of Rice husk in epoxy composites is increased from 37.84 MPa to 48.32 MPa. The experimental results are compared using well-known prediction models such as the rule of mixture (ROM), Halpin–Tsai, and Nielson–Chen using regression analysis with other insulting materials used in state of the art. The Nielson-Chan model predicts experimental data effectively with an average relative error of 14.64%. The proposed composite material has excellent insulating properties because of its conductivity and high dissipation factor. The composite material exhibits high stability when the frequency is in the range of 1–10 kHz than at lower frequencies.